Multifunctional β-NaGdF4:Ln3+ (Ln = Yb, Er, Dy) nanoparticles with NIR to visible upconversion and high transverse relaxivity: a potential bimodal contrast agent for high-field MRI and optical imaging. Issue 66 (27th June 2016) - Biju, Silvanose; Harris, Michael; Elst, Luce Vander; Wolberg, Marike; Kirschhock, Christine; Parac-Vogt, Tatjana N.
Abstract : Developed nano β-NaGdF4 doped with Yb 3+ /Er 3+ in the core and Yb 3+ /Dy 3+ in the shell with favorable properties for combined magnetic resonance and optical imaging. Abstract : A novel series of active-core/active-shell upconverting nanoparticles (AC/AS-UCNPs) based on NaGdF4 doped with Yb 3+ /Er 3+ in the core and Yb 3+ /Dy 3+ in the shell having average particle size between 29.2 and 32.9 nm were synthesized. The UCNPs exhibit favorable properties for bimodal magnetic resonance imaging (MRI) and optical imaging (OI). Excitation of the UCNPs at 980 nm dispersed in water at room temperature resulted in intense green upconversion emission of Er 3+ . The proton nuclear magnetic relaxation dispersion ( 1 H-NMRD) studies show very low longitudinal relaxivity ( r 1 ) values, which decreases with an increase of magnetic field. On the other hand, the transverse relaxivity ( r 2 ) values show an increasing trend with both increase in doping of Dy 3+ as well as the increase in magnetic field reaching a maximum value of r 2 = 70.07 s −1 mM −1 (per Ln 3+ ion) for NaGdF4 :Yb 3+ /Er 3+ # NaYbF4 :38.06% Dy 3+ at 500 MHz and 310 K. Exhibiting such a high r 2 value at high magnetic field and intense upconversion luminescence under 980 nm excitation makes these NPs exceptional candidates towards bioimaging applications.